Distributed photovoltaic supportability consumption method considering energy storage configuration mode and random events - Cui, Yaoqin; Yang, Guobin; Yue, Yan; Zhang, Yibo; Zhao, Tianlong; Chang, Xiaofei (Frontiers in Energy Research, 2024)
In order to improve the control ability of distributed photovoltaic supportability, a distributed photovoltaic supportability consumption method based on energy storage configuration mode and random events is proposed. The networking and constraint parameter analysis model of distributed photovoltaic supportability consumption control is constructed, the AC/DC voltage level control model of distributed photovoltaic supportability consumption is constructed by using the optical storage direct-flexible mode, the source-load uncertainty characteristic parameters of distributed photovoltaic supportability consumption are analyzed by using the demand response tracking identification method in the DC hybrid distribution network operation mode, and the load and photovoltaic output estimation model of distributed photovoltaic supportability consumption is established by combining with the planned energy storage capacity parameter analysis. According to the analysis of uncertainty characteristic parameters of renewable energy output, the optimal capacity of energy storage is configured to fully adjust the power distribution of microgrid. According to the fusion analysis of uncertainty factors of energy storage configuration mode and random events, the design of distributed photovoltaic supportability consumption is realized. The test results show that the distributed photovoltaic absorption control with this method has low load demand, can effectively reduce the exchange power of tie lines, and improve the configuration scale, system reliability and economy of photovoltaic energy storage system.